Applied deep learning with Python : use scikit-learn, TensorFlow, and Keras to create intelligent systems and machine learning solutions /: use scikit-learn, TensorFlow, and Keras to create intelligent systems and machine learning solutions. (2018) - Galea, Alex; Capelo, Luis
No abstract available